Inovasi Model Bisnis Koperasi Merah Putih Berbasis Platform Digital: Implikasi terhadap Tata Kelola dan Kebijakan Perkoperasian - Agus Nugraha (J-Coop : Journal of Co-operative, 2026)
Digital transformation has driven fundamental changes in the ways economic organizations create and distribute value, including cooperatives. However, the development of digital cooperatives in Indonesia remains predominantly focused on technical and operational aspects and has not yet been fully integrated into a comprehensive framework of business models, governance, and cooperative policy. This study aims to analyze innovations in the platform-based business model of Koperasi Merah Putih by positioning digital platforms as institutional architectures that shape value creation, benefit distribution, and power relations within cooperatives. The study employs a qualitative-descriptive approach through a literature review and analysis of policy documents. The findings indicate that digital platforms have the potential to strengthen member participation, governance transparency, and cooperative competitiveness, provided they are designed with collective ownership, democratic governance, and supported by appropriate regulatory and policy frameworks. This study underscores the crucial role of the state in promoting cooperatives as owners and managers of digital platforms to achieve an inclusive, equitable, and public value–oriented digital economic transformation.